Microbial polysaccharides: An emerging family of natural biomaterials for cancer therapy and diagnostics. (November 2022) - Prateeksha; Sharma, Vivek K.; Liu, Xiaowen; Oyarzún, Diego A.; Abdel-Azeem, Ahmed M.; Atanasov, Atanas G.; Hesham, Abd El-Latif; Barik, Saroj K.; Gupta, Vijai Kumar; Singh, Brahma N.
Abstract: Microbial polysaccharides (MPs) offer immense diversity in structural and functional properties. They are extensively used in advance biomedical science owing to their superior biodegradability, hemocompatibility, and capability to imitate the natural extracellular matrix microenvironment. Ease in tailoring, inherent bio-activity, distinct mucoadhesiveness, ability to absorb hydrophobic drugs, and plentiful availability of MPs make them prolific green biomaterials to overcome the significant constraints of cancer chemotherapeutics. Many studies have demonstrated their application to obstruct tumor development and extend survival through immune activation, apoptosis induction, and cell cycle arrest by MPs. Synoptic investigations of MPs are compulsory to decode applied basics in recent inclinations towards cancer regimens. The current review focuses on the anticancer properties of commercially available and newly explored MPs, and outlines their direct and indirect mode of action. The review also highlights cutting-edge MPs-based drug delivery systems to augment the specificity and efficiency of available chemotherapeutics, as well as their emerging role in theranostics.